Identifying Institutional Causes of Delay to Radical Cystectomy among Patients with High Risk Bladder Cancer Treated at a Tertiary Referral Center Using Process Map Analysis. Issue 5 (September 2018) - Almassi, Nima; Glass, Katherine E.; Lonzer, Jennifer L.; Urbanek, Dennis S.; Grivas, Petros; Rini, Brian; Garcia, Jorge; Stephenson, Andrew J.; Klein, Eric A.; Krishnamurthi, Venkatesh
Abstract : Introduction: : Treatment delay among patients with muscle invasive bladder cancer is associated with reduced survival. With limited existing literature examining institutional causes of treatment delay, we identified such causes of delay to radical cystectomy among patients with high risk bladder cancer. Methods: : We conducted a retrospective review of 176 patients with bladder cancer who underwent radical cystectomy at our tertiary referral center in 2013 to 2014. Process mapping was used to define each step in the path to cystectomy and the time interval between each step was quantified. Patients experiencing treatment delay (more than 90 days to cystectomy or chemotherapy initiation) were identified and the causes of delay examined. Results: : Median time from diagnosis to referral was 17 days (IQR 9–36). Following referral the urology and medical oncology evaluations occurred at a median of 5 (IQR 2–9) and 6 days (IQR 1–9), respectively. Median time from urological evaluation to transurethral resection was 14 days (IQR 8–20) and from oncology evaluation to chemotherapy initiation was 9 days (IQR 7–14). Median time to cystectomy for patients proceeding directly from urological evaluation was 28 days (IQR 20–46). Longer intervals were noted from transurethral bladder tumor resection or chemotherapy completion to cystectomy (41 and 44 days, respectively). Overall 24 patients (13.6%) experienced treatment delay. Delays in referral, awaiting preoperative medical clearance, staging studies and surgical scheduling prolonged the time to treatment. Conclusions: : Several institutional factors contribute to treatment delays among patients with bladder cancer. Process mapping allowed characterization of complex paths to cystectomy and identification of causes of treatment delay.